THE EFFECT OF CLIMATE FACTORS FOR DENGUE HEMORRHAGIC FEVER IN BANJARMASIN CITY, SOUTH KALIMANTAN PROVINCE, INDONESIA, 2012-2016 - Ishak, Nuning Irnawulan; Kasman, Kasman (YCAB Publisher & IAKMI SULTRA, 2018)
Background: One of the factors that lead to high incidence of DHF is climate change.Objective: To analyze the effect of climate factors (temperature, humidity, wind speed, and rainfall) associated with DHF incidence in Banjarmasin City, 2012-2016. Methods: We used the national data on annual reported incidence from Health Office of Banjarmasin City and climate variations from Meteorology Climatology and Geophysics Agency 2nd Class Climatology Station Syamsudin Noor Banjarmasin, January 2012-December 2016. The analysis techniques using path analysis to explained the mechanism of causal relationships between variables.Results: The result showed the overall incidence of DHF in Banjarmasin City during 2012- 2016 was 243 cases, of DHF cases were fluctuates by the monthly trend, where the highest number of DHF cases in January to March, climate variation which occurred in Banjarmasin City period 2012-2016 included temperatures ranged from 25.8-28.7°C, humidity ranged from 65-88%, wind speed ranged from 4-6 knots and rainfall ranged from 0.0-546.7 mm, and the path analysis showed that rainfall variable (X4) was the only variable which positively effected to DHF incidence variable (Y) equal to 0.613 unit (Y = 0.613 X4) (p value = 0.002).Conclusion: Climate information can used as a precautionary signal through early warming of the readiness in facing the outbreaks of vector borne diseases so that further efforts in environmental management by manipulation method and environmental modification.